Evidence for capitation reform in a New Rural Cooperative Medical Scheme in Pudong New Area, Shanghai: A longitudinal study. (14th July 2017) - Wang, Yanmei; Shu, Zhiqun; Gu, Jianjun; Sun, Xiaoming; Jing, Limei; Bai, Jie; Huang, Xuan; Lou, Jiquan; Zhang, Qunfang; Li, Ming
Abstract: Currently, China has been experiencing rapid growth of medical costs, serious waste of medical resources, increasing disease burden for residents, and a medical insurance fund deficit. Therefore, an urgent problem that needs to be solved is to choose a rational payment for the insurance system. To empirically evaluate the long‐term effects of capitation reform in a New Rural Cooperative Medical Scheme in Pudong New Area, we collected and analysed data regarding financing, fund operation, medical service cost, and medical care–seeking behaviour from 2011 to 2015, a duration that includes data before and after reform. The data for financing and behaviours were compared year by year, and the monthly data for inpatient and outpatient costs were evaluated in a retrospective time series study. The capitation reform in Pudong New Area showed strong evidence of the power of medical cost control in the long run, while it was weak in reversing the number of patients flowing into secondary and tertiary hospitals. To make the payment of capitation play a bigger role in cost control in China, a tighter alignment of capitation with the general practitioner system and achieving dual referral is critical for future studies.